Pembinaan Kajian Keagamaan Berbasis Karakter Islami pada Majelis Taklim Lowokwaru - Danial Hilmi; Nur Toifah; Erna Herawati (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
This study aims to provide an overview related to the development of religious culture among Majelis Taklim Tunggul Wulung, Lowokwaru, Malang City, where urban communities are in fact educated communities, but are not accompanied by adequate religious understanding. In the meantime, fostering religious studies is important to form Islamic societies. The method used is Participatory Action Research, a study that is accompanied by concrete actions through a form of active participation to be part of the community with the aim of ultimately changing patterns that are less productive. The form of religious culture development in this fostering is carried out counseling and mentoring religious traditions by way of routine study of kitab Salaf as well as simulating the practice procedures for carrying out religious traditions that are in line with Islamic values and emphasizing good attitudes and character. As for the results of this coaching that there is a change in society about increasing religious knowledge and insights specifically womanhood which is always a daily problem, and this coaching is running intensively and is always followed by most residents.